Parenchymal and Functional Lung Changes after Stereotactic Body Radiotherapy for Early-Stage Non-Small Cell Lung Cancer—Experiences from a Single Institution - Hörner-Rieber, Juliane; Dern, Julian; Bernhardt, Denise; König, Laila; Adeberg, Sebastian; Verma, Vivek; Paul, Angela; Kappes, Jutta; Hoffmann, Hans; Debus, Juergen; Heussel, Claus P.; Rieken, Stefan (Frontiers in Oncology, 2017)
Abstract: Introduction: This study aimed to evaluate parenchymal and functional lung changes following stereotactic body radiotherapy (SBRT) for early-stage non-small cell lung cancer (NSCLC) patients and to correlate radiological and functional findings with patient and treatment characteristics as well as survival. Materials and methods: Seventy patients with early-stage NSCLC treated with SBRT from 2004-2015 with more than one year of CT follow-up scans were analyzed. Incidence, morphology, severity of acute and late lung abnormalities as well as pulmonary function changes were evaluated and correlated with outcome. Results: Median follow-up time was 32.2 months with 2-year overall survival (OS) of 83% and local progression-free survival (LPFS) of 88%, respectively. Regarding parenchymal changes, most patients only developed mild to moderate CT abnormalities. Mean ipsilateral lung dose (MLD) in biological effective dose (BED) and planning target volume (PTV) size were significantly associated with maximum severity score of parenchymal changes (p=0.014, p<0.001). Furthermore, both maximum severity score as well as MLD were significantly connected with OS in univariate analysis (p= 0.043, p=0.025). For functional lung changes, we detected significantly reduced total lung capacity (TLC), forced expiratory volume in 1 second (FEV1) and forced vital capacity (FVC) parameters after SBRT (p≤0.001). Multivariate analyses revealed SBRT with a MLD ≥ 9.72 Gy and FVC reduction ≥ 0.54l as independent prognostic factors for inferior OS (p= 0.029, p=0.004). Conclusions: SBRT was generally tolerated well with only mild toxicity. For evaluating the possible prognostic impact of MLD and FVC reduction on survival detected in this analysis, larger prospective studies are truly needed.